Effect of prone positioning on inflammatory markers in blood and lungs: a retrospective cohort study in COVID-19-related ARDS - Hu, Chao; Peng, Li; Liu, Kang; Yang, Li; Zhang, Ying; Deng, Hui; Li, Hui; Jiang, Ming Yan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionProne positioning is a commonly recommended intervention in clinical practice to enhance oxygenation in COVID-19 patients with ARDS, but its effects on inflammatory markers in the blood and lungs have not been thoroughly investigated.MethodsThis retrospective study examined COVID-19-related ARDS patients admitted to the ICU of a tertiary hospital between January 2020 and November 2023. The analysis focused on measuring cytokines and lymphocyte subsets in both blood and bronchoalveolar lavage fluid (BALF) to evaluate the impact of prone positioning on inflammatory markers in the lungs and systemic circulation.ResultsOf the 86 intubated patients, 44 were included in the study, with 30 undergoing prone positioning. Compared to the supine position, prone positioning was associated with elevated plasma levels of IL-12p70 and IL-4, as well as increased expression of IFN-α and TNF-α in BALF. With increased frequency of prone positioning, oxygenation progressively improved, accompanied by a rise in plasma IL-4 levels. No significant differences in peripheral blood lymphocyte levels were observed between the supine and prone groups.ConclusionThis study sheds light on the potential mechanisms of prone positioning in both local and systemic circulation, particularly in the context of inflammatory markers. In COVID-19-related ARDS, prone positioning may strengthen the immune response by modulating inflammatory markers in the lungs and bloodstream.